DSD and Professionalism from a Multilateral View: Supplementing the Consensus Statement on the Basis of a Qualitative Survey - Jürg C. Streuli; Birgit Köhler; Knut Werner-Rosen; Christine Mitchell (Advances in Urology)
Treatment and support of a child with DSD calls for experience and expertise in diagnosis, surgical techniques, understanding of psychosocial issues, and recognizing and accepting the significance of individual values of children, families, and support groups. The range of what is considered “appropriate” care and treatment is still very broad and critics point at major gaps between ethical guidelines and current clinical practice. Based on a qualitative study with 27 members of multidisciplinary teams and support groups, we supplement the professional consensus statements and current ethical guidelines with 14 requirements from four different perspectives, to characterize more fully the responsible treatment and support of children and families affected by DSD. Overall, our findings highlight the importance of close collaborations between different experts and a shift from the often simplified dispute about genital surgeries to a more holistic perspective with a long-term management strategy, which should serve as a cornerstone not only for clinical practice but also for future research and evaluation studies.